2020
DOI: 10.1038/s41467-019-13950-4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological polyamine catabolism upregulation with methionine salvage pathway inhibition as an effective prostate cancer therapy

Abstract: Prostatic luminal epithelial cells secrete high levels of acetylated polyamines into the prostatic lumen, sensitizing them to perturbations of connected metabolic pathways. Enhanced flux is driven by spermidine/spermine N1-acetyltransferase (SSAT) activity, which acetylates polyamines leading to their secretion and drives biosynthetic demand. The methionine salvage pathway recycles one-carbon units lost to polyamine biosynthesis to the methionine cycle to overcome stress. Prostate cancer (CaP) relies on methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 48 publications
0
35
0
Order By: Relevance
“…Recent studies have demonstrated in prostate cancer enhanced metabolic flux of acetylated polyamines to the epithelium in addition to the high demand for polyamine synthesis. This suggested a metabolic sensitivity due to heavy reliance on methionine cycle and methionine salvage pathway which recycles one carbon unit obtained during polyamine biosynthesis 50 . Pharmacological inhibition of the methionine salvage pathway and polyamine acetylation led to reduced tumor growth demonstrating the potential of employing therapies that target metabolic vulnerabilities 50 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated in prostate cancer enhanced metabolic flux of acetylated polyamines to the epithelium in addition to the high demand for polyamine synthesis. This suggested a metabolic sensitivity due to heavy reliance on methionine cycle and methionine salvage pathway which recycles one carbon unit obtained during polyamine biosynthesis 50 . Pharmacological inhibition of the methionine salvage pathway and polyamine acetylation led to reduced tumor growth demonstrating the potential of employing therapies that target metabolic vulnerabilities 50 .…”
Section: Discussionmentioning
confidence: 99%
“…This suggested a metabolic sensitivity due to heavy reliance on methionine cycle and methionine salvage pathway which recycles one carbon unit obtained during polyamine biosynthesis 50 . Pharmacological inhibition of the methionine salvage pathway and polyamine acetylation led to reduced tumor growth demonstrating the potential of employing therapies that target metabolic vulnerabilities 50 . Furthermore, in mesothelioma the absence of arginine biosynthetic pathway was found to compensate for polyamine levels though elevated polyamine synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, spermine synthase (SPMS) transfers an aminopropyl group to spermidine. Spermine oxidase (SMO) directly catalyzes the conversion of spermine to spermidine, and both spermidine/spermine N 1 -acetyltransferase (SSAT) and acetylpolyamine oxidase (APAO) catalyze the conversion of spermine into spermidine and spermidine into putrescine [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, knockdown or inhibition of MTAP (S-methyl-5 -thioadenosine phosphorylase) by shRNA or treatment with Methylthio-DADMe-Immucillin-A (MTDIA) blocks androgen sensitive prostate cancer growth in vivo, suggesting this methionine salvage pathway is important for PCa cell survival [114]. Furthermore, activation of polyamine catabolism by the polyamine analog BENSpm and concomitant inhibition of MTAP by MTDIA synergistically block cell proliferation and provoke cell death in PCa cells ex vivo and in vivo [115]. In this scenario, BENSpm augments SSAT enzyme activity to produce acetylated polyamines, promotes export of acetylated polyamines [116,117], and also leads to depletion of intracellular polyamines [118], increasing demand for polyamine synthesis.…”
Section: Control Of Polyamine Homeostasis and Interacting Metabolic Pathways In Cancermentioning
confidence: 99%
“…It is also important to note that stress that is generated by metabolic perturbations are often context dependent. In the aforementioned study of Affronti et al [115], where PCa cells have intrinsically high polyamine metabolic flux and rely on the methionine salvage pathway, pharmacological inhibition of the methionine salvage pathway depletes SAM pools and suppresses polyamine synthesis. In contrast, in other tumor cell types defects in the methionine salvage pathway augments polyamine levels [119].…”
Section: Control Of Polyamine Homeostasis and Interacting Metabolic Pathways In Cancermentioning
confidence: 99%